Inhibition of Na+-K+-2Cl- Cotransporter-1 attenuates traumatic brain injury-induced neuronal apoptosis via regulation of Erk signaling. (March 2016) - Hui, Hao; Rao, Wei; Zhang, Lei; Xie, Zhen; Peng, Cheng; Su, Ning; Wang, Kai; Wang, Li; Luo, Peng; Hao, Ye-lu; Zhang, Sai; Fei, Zhou
Abstract: Traumatic brain injury (TBI) is the leading cause of mortality and morbidity worldwide and is characterized by immediate brain damage and secondary injuries, such as brain edema and ischemia. However, the exact pathological mechanisms that comprise these associated secondary injuries have not been fully elucidated. This study aimed to investigate the role of the Na + -K + -2Cl - cotransporter-1 (NKCC1) in the disruption of ion homeostasis and neuronal apoptosis in TBI. Using a traumatic neuron injury (TNI) model in vitro and a controlled cortex injury (CCI) model in vivo, the present study investigated changes in the expression and effects of NKCC1 in TBI using western blot, RNA interference, a lactate dehydrogenase (LDH) release assay, TdT-mediated dUTP Nick end-labeling (TUNEL) analysis, sodium imaging, brain water content, and neurological severity scoring. TBI induced the expression of NKCC1 to be significantly upregulated in the cortex, both in vitro and in vivo . Pharmacological inhibitor bumetanide (Bume) or NKCC1 RNA interference significantly attenuated TBI-induced intracellular Na + increase, inhibited neuronal apoptosis, and improved brain edema and neurological function. Furthermore, NKCC1 inhibition also significantly inhibited TBI-induced extracellular signal-regulated kinase (Erk) activation. Erk inhibition significantly protected neurons from TBI injury; however, Erk inhibition had no effect on NKCC1 expression or the neuroprotective effect of NKCC1 inhibition against TBI. This study demonstrates the role of NKCC1 in TBI-induced brain cortex injury, establishing that NKCC1 may play a neurotoxic role in TBI and that the inhibition of NKCC1 may protect neurons from TBI via the regulation of Erk signaling. Highlights: TBI upregulated the expression of NKCC1 and p-Erk in vitro and in vivo . Inhibition of NKCC1 protected against TBI-induced [Na + ]i increase. Inhibition of NKCC1 alleviated TNI-induced neuronal apoptosis. Inhibition of NKCC1 improved CCI-induced brain injury. Erk Inhibitor had no effects on NKCC1 and neuroprotection of NKCC1 inhibiting.